Review: Gambaran Aktivitas Enzim Alkaline Phosphatase (ALP) pada Pemain Game Online di Kecamatan Jekan Raya Kota Palangka Raya - Oktavia Vivin Ermanita; Ria Agustina Handayani; Eki Muharamah; Dwi Purbayanti (Borneo Journal of Medical Laboratory Technology, 2020)
An online game is a game that is played using an internet network. Online games can cause addictions, which result in changes in sleep patterns that can disrupt circadian rhythms. The body produces more free radicals and causes oxidative stress, which can attack hepatocyte cells. To assess liver function abnormalities, one of them can be known by checking the enzyme Alkaline Phosphatase (ALP). This study aimed to determine the activity of the Alkaline Phosphatase (ALP) enzyme in Online game players in the city of Palangka Raya. This research was conducted with a descriptive method using the Snowball Sampling technique, and the sample in this study amounted to 50 people. From the results of the examination of the activity of the enzyme Alkaline Phosphatase (ALP), ALP values ​​were obtained above normal 10 people (20%).